DN25: An adaptive quantum cryptography protocol for secure and efficient communication - Darlan Noetzold; de Paz Santana, Juan Francisco; Valderi Leithardt; Jorge Luis Victória Barbosa (Workshop of Research in Science and Engineering, 2026)
Quantum computing challenges classical cryptographic infrastructures and has driven four decades of development in Quantum Key Distribution (QKD) protocols, from BB84 to recent twin‑field and multiparty schemes. However, many existing solutions lack adaptability across heterogeneous deployment scenarios. We introduce DN25, an adaptive cryptographic protocol that integrates QKD, Post‑Quantum Cryptography (PQC), and hybrid approaches, dynamically selecting the most suitable mechanism based on system conditions (device capabilities, distance, performance and security requirements). DN25 aims to balance robustness against quantum‑enabled adversaries with operational efficiency in constrained or high‑throughput environments. We review 20 representative QKD protocols, describe DN25’s architecture, and outline testing and evaluation considerations.